2014
DOI: 10.1164/rccm.201308-1535oc
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Targeting of IL-1 and IL-18 Is Required for Protection against Inflammatory and Septic Shock

Abstract: Our data point toward the therapeutic potential of neutralizing IL-1 and IL-18 simultaneously in sepsis, rather than inhibiting the upstream inflammatory caspases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
71
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(78 citation statements)
references
References 54 publications
7
71
0
Order By: Relevance
“…5D). These results are consistent with previous reports that IL-18 can drive IL-1 and that blockade of both IL-18 and IL-1 is associated with an increase in sepsis survival (11) and substantially bridge the gaps in our mechanistic understanding of how IL-18 participates in this inflammatory pathway.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…5D). These results are consistent with previous reports that IL-18 can drive IL-1 and that blockade of both IL-18 and IL-1 is associated with an increase in sepsis survival (11) and substantially bridge the gaps in our mechanistic understanding of how IL-18 participates in this inflammatory pathway.…”
Section: Resultssupporting
confidence: 92%
“…In contrast, some studies have shown a critical positive role for IL-18 in the adult host response to Pseudomonas pneumonia (3,10). The survival benefits of combined IL-18/ IL-1β targeting were demonstrated recently in septic shock, but that study did not investigate the primary contributor to deleterious outcomes in murine sepsis, nor did they establish the mechanism of effect (11).…”
mentioning
confidence: 98%
“…In contrast to humans mice are inbreed littermates with no genetic variation and cytokine differences should have been detected. Other studies could detect differences in TNF-α expression between KO and wild type mice of other genes [38]. Therefore AQP5 might not influence TNF-α pathway and other inflammatory proteins might be responsible for the differences occurring in Aqp5 -KO and WT animals.…”
Section: Discussionmentioning
confidence: 98%
“…Consistent with this, LPS-injected caspase-4 transgenic mice secreted higher levels of IL-1β and IL-18 initially, and interestingly, in contrast to in vitro assay, other cytokines were significantly induced, indicating the presence of complex cytokine cross-stimulation between cells and tissues in vivo . More recently, secretion of IL-1β and IL-18 has been shown to contribute to lethality induced by low doses of LPS in mice (37), although they may not mediate lethality to high doses of LPS (14). Our data showing that the secretion of IL-1β and IL-18 represents an immediate early response in caspase-4 transgenic mice may partially explain the mechanism of the increased lethality (Fig.…”
Section: Discussionmentioning
confidence: 99%